Multi-product inventory modeling with demand forecasting - Mendoza Bojorquez, Axel Abraham (2025)
Many wholesale companies do not use an adequate control of their inventory level, and variables such as product demand tend to vary continuously due to seasonality and market trends, generating costs that reduce profitability and eventually produce customer dissatisfaction with the service offered. In this paper we propose the application of a methos to reduce the level of uncertainty and risk in sales and to simulate the implementation of a policy of continuous inventory review. Using the monthly demand of the wholesale company and considering the maximization of profit, the ARIMA time series model was chosen, developed through the R programming language, and then modeled in the Arena software the results of the forecast found. The relevance of the study is to present inventory improvement tools that encourage a favorable management in terms of inventory management costs.